1989
DOI: 10.1144/gsl.sp.1989.043.01.20
|View full text |Cite
|
Sign up to set email alerts
|

The Precambrian mobile belt of southern Madagascar

Abstract: The Precambrian of southern Madagascar consists largely of medium- and high-grade paragneisses and metasediments that have a predominantly north-south regional trend, which is parallel to that of the Mozambique belt of eastern Africa. The Precambrian geology of Madagascar is synthesized by Besairie (1971) and Hottin (1976). Much mineralogical information of relevance to metamorphic petrology is given by Lacroix (1922–23). Nicollet (1985, 1986) gives good metamorphic and P-T data from Ih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…These mostly have peak P-T estimates of 0.6-1.0 GPa and 850-1000°C with decompression-dominated clockwise P-T paths (Ackermand et al, 1989;Markl et al, 2000;Jöns and Schenk, 2011;Boger et al, 2012). Horton et al (2016) argued that peak T was >900°C in the south-central Anosyen Domain and decreased to the north and west, whereas earlier estimates of 0.3-0.5 GPa and 650-850°C for the Anosyen Domain (Nicollet, 1990;Martelat et al, 1999) are likely a retrograde overprint.…”
Section: Metamorphism Between the Suturesmentioning
confidence: 98%
“…These mostly have peak P-T estimates of 0.6-1.0 GPa and 850-1000°C with decompression-dominated clockwise P-T paths (Ackermand et al, 1989;Markl et al, 2000;Jöns and Schenk, 2011;Boger et al, 2012). Horton et al (2016) argued that peak T was >900°C in the south-central Anosyen Domain and decreased to the north and west, whereas earlier estimates of 0.3-0.5 GPa and 650-850°C for the Anosyen Domain (Nicollet, 1990;Martelat et al, 1999) are likely a retrograde overprint.…”
Section: Metamorphism Between the Suturesmentioning
confidence: 98%
“…At the northern part of this belt south of Beraketa we have observed abundant discordant, partly deformed amphibolite dykes in hypersthene gneiss; these relations point to an early granulite facies metamorphism followed by dyke intrusion and then by amphibolite facies metamorphism. Ackermand et al (1989) reported a steep, nearly isothermal P-T trajectory from 10 to 4 kbar at 1000-800°C at Vohidava (Fig. 5); the reaction of enstatite + sillimanite to sapphirine + cordierite indicates early, very high temperature, granulite facies metamorphism above 9.5 kbar and 950°C.…”
Section: Southern Madagascarmentioning
confidence: 98%
“…The Betroka belt contains amphibolite dykes that post-date granulite facies gneisses, and also petrographic evidence of relict (undated), very early high temperature metamorphism with orthopyroxene above 950°C and 9.5 kbar (Ackermand et al, 1989). The gneisses of the Tranomaro belt contain gneissic, migmatitic granite sheets that crystallized at 565 Ma contemporaneous with granulite facies metamorphism associated with the synmetamorphic emplacement of the 570 Ma Anosyan charnockites and granites in the nearby Fort Dauphin-Anosyan belt (Paquette et al, 1994).…”
Section: Southern Madagascarmentioning
confidence: 99%
“…Windley et al 1994;Martelat 1998;Martelat et al 2000;Nédélec et al 2000) that formed at high-grade metamorphic conditions during the late stages of the East African Orogen (Nicollet 1990;Martelat et al 1997;de Wit et al 2001). Although the steep ductile zones predominantly strike N-S (present-day coordinates), previous workers also postulated a NW-SE striking ductile shear zone that traverses the entire crystalline basement of southern Madagascar (e.g., Katz and Premoli 1979;Ackermand et al 1989;Martelat 1998). This zone is generally referred to as the Ranotsara shear zone, but has previously also been termed Ranotsara-Ranomena lineament (Katz and Premoli 1979), Ranotsara shear belt (Ackermand et al 1989) or Bongolava-Ranotsara shear zone (Caen-Vachette 1979;Martelat 1998;Lardeaux et al 1997Lardeaux et al , 1999Müller 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although the steep ductile zones predominantly strike N-S (present-day coordinates), previous workers also postulated a NW-SE striking ductile shear zone that traverses the entire crystalline basement of southern Madagascar (e.g., Katz and Premoli 1979;Ackermand et al 1989;Martelat 1998). This zone is generally referred to as the Ranotsara shear zone, but has previously also been termed Ranotsara-Ranomena lineament (Katz and Premoli 1979), Ranotsara shear belt (Ackermand et al 1989) or Bongolava-Ranotsara shear zone (Caen-Vachette 1979;Martelat 1998;Lardeaux et al 1997Lardeaux et al , 1999Müller 2000). It is generally regarded as a *20-km-wide intra-crustal strike-slip shear zone (Martelat et al 2000) with a sinistral sense of shear (e.g.…”
Section: Introductionmentioning
confidence: 99%